Flexible and Wearable All‐Solid‐State Supercapacitors with Ultrahigh Energy Density Based on a Carbon Fiber Fabric Electrode. Issue 20 (14th July 2017) - Qin, Tianfeng; Peng, Shanglong; Hao, Jiaxin; Wen, Yuxiang; Wang, Zilei; Wang, Xuefeng; He, Deyan; Zhang, Jiachi; Hou, Juan; Cao, Guozhong
Abstract: Wearable textile energy storage systems are rapidly growing, but obtaining carbon fiber fabric electrodes with both high capacitances to provide a high energy density and mechanical strength to allow the material to be weaved or knitted into desired devices remains challenging. In this work, N/O‐enriched carbon cloth with a large surface area and the desired pore volume is fabricated. An electrochemical oxidation method is used to modify the surface chemistry through incorporation of electrochemical active functional groups to the carbon surface and to further increase the specific surface area and the pore volume of the carbon cloth. The resulting carbon cloth electrode presents excellent electrochemical properties, including ultrahigh areal capacitance with good rate ability and cycling stability. Furthermore, the fabricated symmetric supercapacitors with a 2 V stable voltage window deliver ultrahigh energy densities (6.8 mW h cm −3 for fiber‐shaped samples and 9.4 mW h cm −3 for fabric samples) and exhibit excellent flexibility. The fabric supercapacitors are further tested in a belt‐shaped device as a watchband to power an electronic watch for ≈9 h, in a heart‐shaped logo to supply power for ≈1 h and in a safety light that functions for ≈1 h, indicating various promising applications of these supercapacitors. Abstract : Carbon fiber textile is fabricated and employed to assemble high‐performance flexible and wearable all‐solid‐state supercapacitor with much enhanced energy density and mechanical strength to allow the electrode material to be weaved into desired devices, such as a watchband to power an electronic watch for ≈9 h, indicating a promising application.